2010
DOI: 10.1371/journal.pone.0012921
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of E-Cadherin-Mediated Cellular Aggregation Allows Proliferation of Pluripotent Mouse Embryonic Stem Cells in Shake Flask Bioreactors

Abstract: BackgroundA fundamental requirement for the exploitation of embryonic stem (ES) cells in regenerative medicine is the ability to reproducibly derive sufficient numbers of cells of a consistent quality in a cost-effective manner. However, undifferentiated ES cells are not ideally suited to suspension culture due to the formation of cellular aggregates, ultimately limiting scalability. Significant advances have been made in recent years in the culture of ES cells, including automated adherent culture and suspens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 32 publications
1
42
1
Order By: Relevance
“…Although mESCs share similarities with hESCs, they differ in several major aspects (Hirai et al, 2011). This includes that stemness in mESCs is insensitive to cell-cell dissociation (Mohamet et al, 2010). p120-catenin depletion destabilizes Ecadherin (Davis et al, 2003), often resulting in altered cell-cell interactions.…”
Section: P120-catenin In Modulating Stemness and Differentiationmentioning
confidence: 99%
“…Although mESCs share similarities with hESCs, they differ in several major aspects (Hirai et al, 2011). This includes that stemness in mESCs is insensitive to cell-cell dissociation (Mohamet et al, 2010). p120-catenin depletion destabilizes Ecadherin (Davis et al, 2003), often resulting in altered cell-cell interactions.…”
Section: P120-catenin In Modulating Stemness and Differentiationmentioning
confidence: 99%
“…However, our data in E-cadherin-/-ES cells demonstrated that these cells could be cultured in static suspension culture and maintain pluripotent marker expression over 30d (Mohamet et al, 2010). Furthermore, we have recently demonstrated that wild type mES cells can be cultured as a near single cell suspension over prolonged periods in scalable shake flasks in the absence of additional media supplements (Mohamet et al, 2010). Using the E-cadherin neutralising antibody DECMA-1 we have shown that wtES cells exhibit doubling times of 15.6h±4.7 and mean-fold increase in viable cell numbers over 48h of 16±0.9.…”
Section: Culture Of Mes Cells In Shake Flask Suspension Culture Usingmentioning
confidence: 72%
“…E-cadherin has been demonstrated to be the cause of aggregation of ES cells in suspension culture (Fok and Zandstra, 2005) and several groups have suggested that abrogation of E-cadherin in ES cells results in low cell viability (Fok and Zandstra, 2005) and could adversely affect the pluripotent status of the cells when cultured in bioreactors (Dang et al, 2004). However, our data in E-cadherin-/-ES cells demonstrated that these cells could be cultured in static suspension culture and maintain pluripotent marker expression over 30d (Mohamet et al, 2010). Furthermore, we have recently demonstrated that wild type mES cells can be cultured as a near single cell suspension over prolonged periods in scalable shake flasks in the absence of additional media supplements (Mohamet et al, 2010).…”
Section: Culture Of Mes Cells In Shake Flask Suspension Culture Usingmentioning
confidence: 79%
See 2 more Smart Citations